Giant Cell Granuloma of the Temporal Bone in a Mixed Martial Arts Fighter - Maerki, Jennifer; Riddle, Nicole D.; Newman, Jason; Husson, Michael A.; Lee, John Y.K. (Journal of Neurological Surgery Reports, 2012)
Background and Importance Giant cell granuloma (GCG) is a rare, benign, non-neoplastic lesion of the head and neck. More common in the jaw bones, there have been few reports of the lesion arising in the temporal bone. Initially referred to as a “giant cell reparative granuloma,” due to the previously accepted notion of its nature in attempting to repair areas of injury, the term “giant cell granuloma” is now more frequently used as this lesion has been found in patients without a history of trauma. In addition, several cases with a destructive nature, in contrast to a reparative one, have been observed.Clinical Presentation We report a case of GCG presenting as a head and neck tumor with dural attachments and extension into the middle cranial fossa in a mixed martial arts fighter.Conclusion Giant cell granulomas are typically treated surgically and have a good prognosis; however, care must be taken when they present in unusual locations. This case supports the theory of trauma and inflammation as risk factors for GCG.
Keywords: giant cell reparative granuloma; reactive pseudoneoplasms; giant cell; reparative granuloma